UPAYA MENINGKATKAN KEMAMPUAN SANTRI DALAM TILAWAH ALQURAN DI PONDOK PESANTREN MAMBA`UL HUDA KALIABU - Rosad Rosad; Maryono Maryono (Institut Agama Islam Syubbanul Wathon Magelang, 2021)
The form of attention and development of recitation of the Qur'an is one of the extra curricular activities at the Mamba`ul Huda Islamic Boarding School and has been going on since 2010. The obstacles in improving the ability of the recitation are, there are still students who are not fluent in mentioning letters or makharijul letters, and recitation, the absence of special supervision from the management, then the lack of interest, motivation of students. The purpose of this service is to develop and improve students' recitation skills so that they can read the Qur'an properly, correctly according to the rules, and be able to recite the rhythm in reading the Qur'an. This service is carried out using a PAR (Participation Action Research) approach. The method used in the service is on-the-job training or direct practice. The results of this service can help the students of the Mamba`ul Huda Islamic Boarding School in reciting the Koran.